Pengembangan Manajemen Madrasah pada Era Revolusi Industri 4.0 di MAS Miftahussalam - Salsabila Kesuma Haidi; Muhammad Yunan Harahap; Sakban Lubis (Medan Resource Center, 2026)
This study investigates the adaptation of MAS Miftahussalam madrasah management to the challenges of the Industrial Revolution 4.0 in Islamic Religious Education (PAI). Previous studies have largely discussed digital transformation in general education institutions, while limited research specifically examines innovative and sustainable management practices in Islamic madrasahs. Therefore, this study aims to analyze the role of madrasah management, supporting and inhibiting factors, and strategies implemented to strengthen digital-based learning and administration. This research employed a qualitative descriptive method using a field study approach through observations, interviews, and documentation. Data were collected from the madrasah principal, curriculum staff, and PAI teachers, supported by institutional documents such as lesson plans and learning modules. The findings reveal that MAS Miftahussalam has integrated digital technology into both administrative and instructional processes through the use of Quizizz, Canva AI, online examinations, digital attendance systems, and barcode-based tuition payment services. In learning activities, teachers applied interactive digital quizzes, Higher Order Thinking Skills (HOTS)-based discussions, and educational social media content to strengthen students’ moral values. However, several challenges remain, particularly limited digital literacy among some teachers and technical infrastructure constraints. This study contributes to the development of innovative and sustainable madrasah management models that support effective adaptation to the digital era and enhance the quality of Islamic education.